Transformasi Sistem Pembelajaran di Pondok Pesantren Sidogiri - Rohmani, Abd. Hadi (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2017)
Sidogiri is one of the major schools, even the oldest in East Java. In its long history, almost three centuries, Sidogiri remain concerned at the development of Islamic education schools, but by doing a number of innovations in learning systems, both from the aspect of the methods and curriculum. One form of amendments is Aliyah-level learning system with the majors, which is actually a learning system such as this is usually only found in vocational schools and colleges. Until now there are five majors developed by Madrasah Aliyah Sidogiri, namely MT, Dakwah, Tenets, Tafsir and Hadith. Policy Department Sidogiri implementing this system is not born in a vacuum without intent, but rather a manifestation of the jargon that had been held firmly, to preserve the old system are still worth taking and adopt a new system that is more relevant to the times. In fact, in terms of teaching methods, Sidogiri yellow book has reached the point of realizing the new system is better than ever before.